Pengolahan Limbah Tekstil Artifisial (Zat Warna Reaktif) Dengan Proses Oksidasi Katalitik Menggunakan Nano-Mn/Carbon Sphere - Sri Meilani; Edy Saputra; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The latest innovations in the processing of textile waste is using advanced oxidation processes (AOPs) by oxidant capable of generating a radical sulphate (SO4*). The purpose of this research is to determine catalyst activity of Nano-Mn/CS in oxidation process, reduce the dye on using peroxymonosulfate and Nano-Mn/CS, and determine the optimum conditions for reducing the dye in water. Catalytic synthesis process carried out by the hydrothermal process at temperature of 180o C for 18 hours in an autoclave to produce black carbon from D-glucose solution and then it will be impregnated with a variation of 3% and 5% Mn. Then it calcined with N2 at temperature of 500o C for 4 hours. The optimum condition for degradation of methylene blue (artificial wastes) 25 ppm carried out for 120 minutes with 0,2 gr/L catalysts Nano-Mn/CS and 4 gr/L oxone with efficiency of 91.07%.Keywords: AOPs, Methylene blue, Nano-Mn/CS, Peroxymonosulfate